TEOKRASI DAN DEMOKRASI: Komparasi Reflektif Teokrasi Israel Kitab Suci dengan Demokrasi Langsung di Indonesia - Roy Charly Sipahutar (IAKN Ambon, 2018)
This paper is a biblical reflective work that seeks to analyze the connectedness between the theocracy ideas in the Old Testament (Israel) and the Direct Democracy System implemented in Indonesia. It is not denied that the two state systems must have their own context, apart from a great distance and time. However, that does not mean there can not be found a wedge between the two. So with this the author tries to explore any ideal values ??in the theocracy system at the time of Israel Bible that eventually can become a very useful capital for the basic participation of citizens (people) in Indonesia in the direct democratic system. The hope is that people's mood to contribute to their participation in politics can be answered well.